Gambaran Pengetahuan Ibu Hamil Tentang 6 Tanda Bahaya Pada Kehamilan Berdasarkan Buku Kesehatan Ibu Dan Anak Tahun 2020 Di Puskesmas Madising Na Mario - Nurfitri Nurfitri; Ayu Rosanti Wilujeng; Andi Wilda Arianggara; Hasnia Hasnia (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2024)
Pregnant women in Indonesia are required to have a Maternal and Child Health (MCH) Book. The latest edition of the MCH Book was published in 2020, the contents of which are increasingly complete and complex, on page 21 of this book contains a description of 6 Danger Signs in Pregnancy which are very important for a pregnant mother to know and be aware of. This study aims to determine the description of pregnant women's knowledge about the 6 Danger Signs in Pregnancy based on the KIA Book in the working area of ​​the Madising Na Mario Community Health Center. This type of research is descriptive research using primary data collected through a questionnaire instrument. The population in this study was 84 pregnant women and a sample of 51 respondents was obtained (purprosive sampling). This research was carried out from February 13 to March 13 2023. The research results obtained were that 56.9% (29 respondents) of respondents had poor knowledge about the 6 Danger Signs in Pregnancy based on the MCH Book they owned. So it is hoped that pregnant women will pay more attention to the MCH Book they have, not only to record their pregnancy history, but it can also be used as a guidebook during their pregnancy to avoid pregnancy complications.